Resistant rock layers amplify cosmogenically‐determined erosion rates. Issue 2 (8th January 2020) - Darling, Andrew; Whipple, Kelin; Bierman, Paul; Clarke, Brian; Heimsath, Arjun
Abstract: Prior numerical modeling work has suggested that incision into sub‐horizontal layered stratigraphy with variable erodibility induces non‐uniform erosion rates even if base‐level fall is steady and sustained. Erosion rates of cliff bands formed in the stronger rocks in a stratigraphic sequence can greatly exceed the rate of base‐level fall. Where quartz in downstream sediment is sourced primarily from the stronger, cliff‐forming units, erosion rates estimated from concentrations of cosmogenic beryllium‐10 ( 10 Be) in detrital sediment will reflect the locally high erosion rates in retreating cliff bands. We derive theoretical relationships for threshold hillslopes and channels described by the stream‐power incision model as a quantitative guide to the potential magnitude of this amplification of 10 Be‐derived erosion rates above the rate of base‐level fall. Our analyses predict that the degree of erosion rate amplification is a function of bedding dip and either the ratio of rock erodibility in alternating strong and weak layers in the channel network, or the ratio of cliff to intervening‐slope gradient on threshold hillslopes. We test our predictions in the cliff‐and‐bench landscape of the Grand Staircase in southern Utah, USA. We show that detrital cosmogenic erosion rates in this landscape are significantly higher (median 300 m/Ma) than the base‐level fall rate (~75 m/Ma) determined from the incision rate of a trunk stream into a ~0.6 Ma basalt flow emplaced along a 16 km reach of the channel. We infer a 3–6‐fold range in rock strength from near‐surface P‐wave velocity measurements. The approximately four‐fold difference between the median 10 Be‐derived erosion rate and the long‐term rate of base‐level fall is consistent with our model and the observation that the stronger, cliff‐forming lithologies in this landscape are the primary source of quartz in detrital sediments. © 2020 John Wiley & Sons, Ltd. Abstract : We derive a relationship between rock strength ratios and the magnitude that erosion rate changes relative to base level fall in sub‐horizontally bedded stratigraphy. Detrital cosmogenic erosion rate data from the Grand Staircase of the western United States support the existence of enhanced erosion rate relative to base‐level fall at strong over weak contacts that are consistent with derived magnitudes of erosion rate enhancement above the local base level fall rate.